2018
DOI: 10.1016/j.visres.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A spatial frequency spectral peakedness model predicts discrimination performance of regularity in dot patterns

Abstract: Subjective assessments of spatial regularity are common in everyday life and also in science, for example in developmental biology. It has recently been shown that regularity is an adaptable visual dimension. It was proposed that regularity is coded via the peakedness of the distribution of neural responses across receptive field size. Here, we test this proposal for jittered square lattices of dots. We examine whether discriminability correlates with a simple peakedness measure across different presentation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…8A), i.e. lower SFs, as seen earlier [16]. Increasing element size pushes the high peak to the right, toward higher SFs (Fig.…”
Section: Regularity Model Based On the Sf Distributionsupporting
confidence: 78%
See 1 more Smart Citation
“…8A), i.e. lower SFs, as seen earlier [16]. Increasing element size pushes the high peak to the right, toward higher SFs (Fig.…”
Section: Regularity Model Based On the Sf Distributionsupporting
confidence: 78%
“…It is made Implications for the use of MLCM Our study provides a new ANOVA-based statistical framework for using three-factor MLCM. Traditional MLCM has provided a framework for handling only two factors, comparing a full vs. additive model [16]. The main goal for the traditional MLCM approach has been to determine whether the two factors contribute to a perceptual judgment additively or in a nonlinear manner.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these SF models, it is expected that other factors which change the SF-distribution parameters, in addition to the widely used jittering of element position [ 5 7 , 13 , 14 ], may potentially affect regularity perception. For example, increasing element size can increase SF-peakedness substantially, and as expected, regularity discriminability is enhanced [ 16 ]. Element spacing can also affect SF-peakedness, but the peak in the SF-response distribution related to spacing might overlap with the peak from size, giving two separate peaks [ 16 ] or a composite peak if they overlap.…”
Section: Introductionmentioning
confidence: 74%
“…In line with the above studies, researchers have suggested that the peakedness of the distribution of oriented spatial frequency-tuned filter responses might help explain regularity encoding [ 5 , 6 , 16 ]. Based on these studies as well as evidence from our simultaneous regularity contrast study [ 7 ], we suggested that in addition to SF-peakedness, other statistics of the SF-distribution–such as the bandwidth (width at half maximum, FWHM), kurtosis, skew and standard deviation–are also good predictors of perceived regularity, and could therefore be used for coding regularity in the visual system.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation